Influence of working capital metrics on profitability: a critical examination on Indian manufacturing sector - Aravind, M. (University of Kelaniya, 2016)
The disbursement of working capital is usually considered as a short term cash flow and it is totally neglected by the policy makers to tag with profitability of a concern. Usually the variation in working capital will be observed at the end of the financial year. Such observations will be just a postmortem of financial events happened. Various metrics like Cash Conversion Cycle (CCC), Net Trade Cycle etc directly or indirectly controlling profitability of business. This work investigates how various working capital metrics influencing profitability of the firms by observing a data set of 100 manufacturing companies in India. This study comprehends ten year financial data from the FY 2005-06 to the FY 2014-15. All together a balanced panel set of 1000 firm-year observations form part of this research. The data analysis was carried out using both descriptive and inferential statistical measures. The results show that CCC is positively correlated to Net profit Ratio (NPR) but negatively related to the Return on Equity (ROE). Another major fact identified that the Indian manufacturing firms are having a high DPO (Days Payable Outstanding) while maintaining a moderate DSO (Days Sales Outstanding) and DIO (Days Inventory Outstanding). This situation spots towards the fact that the manufacturing firms are enjoying liberal credit policy from their suppliers. The study also looks into the impact of working capital on profitability at distinct economic phases. The result concludes that the influence of working capital on profitability was consistent irrespective of the economic cycle.
Keywords: Cash Conversion Cycle; Net Trade Cycle; Profitability Measures